Jun N‐terminal kinase activity is required for invagination but not differentiation of the sea urchin archenteron. Issue 12 (6th December 2015) - Long, Jason T.; Irwin, Leslie; Enomoto, Addison C.; Grow, Zachary; Ranck, Jessica; Peeler, Margaret T.
Summary: Although sea urchin gastrulation is well described at the cellular level, our understanding of the molecular changes that trigger the coordinated cell movements involved is not complete. Jun N‐terminal kinase (JNK) is a component of the planar cell polarity pathway and is required for cell movements during embryonic development in several animal species. To study the role of JNK in sea urchin gastrulation, embryos were treated with JNK inhibitor SP600125 just prior to gastrulation. The inhibitor had a limited and specific effect, blocking invagination of the archenteron. Embryos treated with 2 μM SP600125 formed normal vegetal plates, but did not undergo invagination to form an archenteron. Other types of cell movements, specifically ingression of the skeletogenic mesenchyme, were not affected, although the development and pattern of the skeleton was abnormal in treated embryos. Pigment cells, derived from nonskeletogenic mesenchyme, were also present in SP600125‐treated embryos. Despite the lack of a visible archenteron in treated embryos, cells at the original vegetal plate expressed several molecular markers for endoderm differentiation. These results demonstrate that JNK activity is required for invagination of the archenteron but not its differentiation, indicating that in this case, morphogenesis and differentiation are under separate regulation. genesis 53:762–769, 2015. © 2015 Wiley Periodicals, Inc.